Galatians - Schreiner, Thomas R. (Grand Rapids, Mich. : Zondervan, 2010)
"In this newest volume of the Zondervan Exegetical Commentary on the New Testament series, Thomas R. Schreiner offer pastors, students, and teachers a focused resource for reading Galatians. Through the use of graphic representations of translations, succinct summaries of main ideas, exegetical outlines, and other features, Schreiner presents Paul's Epistle to the Galatians with precision and accuracy. Designed for the pastor and Bible teacher, this series brings together commentary features rarely gathered together in one volume. Written by notable evangelical scholars, each volume in the Zondervan Exegetical Commentary on the New Testament series treats the literary context and structure of the passage in the original Greek. The series consistently provides the main point, an exegetical outline, verse-by-verse commentary, and theology in application in each section of every commentary. Critical scholarship informs each step but does not dominate the commentary, allowing readers to concentrate on the biblical author's message as it unfolds. While primarily designed for those with a basic knowledge of biblical Greek, all who strive to understand and teach the New Testament will find these books beneficial. The ZECNT series covers the entire New Testament in twenty volumes; Clinton E. Arnold serves as general editor. In this volume, Thomas R. Schreiner offers pastors, students, and teachers a focused resource for reading Galatians. Through the use of graphic representations of translations, succinct summaries of main ideas, exegetical outlines and other features, Schreiner presents Paul's Epistle to the Galatians with precision and accuracy. Because of this series' focus on the textual structure of the scriptures, readers will better understand the literary elements of Galatians, comprehend the author's revolutionary goals, and ultimately discover their vital claims upon the church today" -- Publisher description.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries